The radioprotector ortho-phospho-L-tyrosine (pTyr) attenuates the side effects of fractionated irradiation in retinoblastoma mouse models but also decreases the local tumour control. Issue 3 (September 2017) - Tschulakow, Alexander V.; Dittmann, Klaus; Huber, Stephan M.; Klumpp, Dominik; Stegen, Benjamin; Schraermeyer, Ulrich; Rodemann, H. Peter; Julien-Schraermeyer, Sylvie
Abstract: Background: Radiotherapy (RT) is used to treat retinoblastoma (Rb), the most frequent ocular tumour in children. Besides eradicating the tumour, RT can cause severe side effects including secondary malignancies. This study aimed to define whether the radioprotector ortho-phospho-L -tyrosine (pTyr) prevents RT-induced side effects and affects local tumour control in a xeno graft and a genetic orthotopic Rb mouse model. Methods: B6;129-Rb1tm3Tyj/J (Rb +/− ) and Y79-Rb cell- xeno grafted nude mice were fractionated external beam irradiated (15 fractions of 5 Gy 6 MV photons during 3 weeks) with or without pTyr pre-treatment (100 mg/kg BW, 16 h prior to each irradiation). One, three, six and nine months after RT, tumour control and RT toxicity were evaluated using in vivo imaging and histology. We also analysed pTyr dependant post irradiation cell survival and p53 activity in vitro . Results: In vitro pTyr pre-treatment showed no radioprotection on Y79 cells, but led to p53 stabilisation in unirradiated Y79 cells and to a facilitation of radiation-induced p21 up-regulation, confirming a modulation of p53 activity by pTyr. In both mouse models, secondary tumours were undetectable. In Rb +/− mice, pTyr significantly lowered RT-induced greying of the fur, retinal thickness reduction and photoreceptor loss. However, in the xeno grafted Rb model, pTyr considerably decreased RT-mediated tumour control, which was observed in 16 out of 22 control eyes but in none of the 24 pTyr treated eyes. Conclusions: In Rb +/− mice pTyr significantly prevents RT-induced greying of the fur as well as retinal degeneration. However, since non-irradiated control mice were not used in our study, a formal possibility exists that the effect shown in the retina of Rb +/− mice may be due to ageing of the animals and/or actions of pTyr alone. Unfortunately, as tested in a xeno graft model, pTyr treatment reduced the control of Rb tumours.